Digitalisasi Proses Survei Badan Litbang dan Diklat Kementerian Agama Republik Indonesia Melalui Pembuatan Aplikasi E-Survey Berbasis Web - Fazhli Ridwan Husbi; Arief Ichwani (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2024)
In the era of globalization with rapid technological advancements, government agencies must actively keep up with these developments. Badan Litbang dan Diklat Kementerian Agama Republik Indonesia (RI) faces challenges in the survey data collection process, which is still conducted manually. This manual method leads to delays in data collection, potential data input errors, risk of data loss, and difficulties in efficient data management. This research aims to design and implement a web-based e-survey application using Laravel technology to assist the Badan Litbang dan Diklat Kementerian Agama RI in collecting survey data more efficiently and accurately. The application is expected to build a better survey system, enhance operational efficiency, and facilitate analysis and decision-making based on the collected survey data. The development of this application uses the Extreme Programming (XP) methodology, which allows the development team to quickly adapt to changing requirements, improve software quality, and ensure active stakeholder involvement. The results of this research are expected to help the Badan Litbang dan Diklat Kementerian Agama RI improve data collection efficiency, reduce recording errors, and provide quick access to survey results. Consequently, this agency can optimize their survey data collection processes more effectively